A DEA approach for measuring healthcare efficiency in medical, clinical and obstetric specialties - Fabrício da Silva Santos; Susane de Farias Gomes (Socioeconomic Analytics)
Alagoas occupies the worst public health positions in Brazil, and first in the indicators of infant mortality, presenting an extremely high mortality rate (48.2 deaths per thousand live births to a Brazilian average of 26.3 deaths per thousand live births). Such problem highlights the need for quantitative methodologies in order to evaluate the technical efficiency of state health units in search of continuous improvement of their results. The present study develops an efficiency analysis of several public and private hospitals located in the state of Alagoas using the Data Envelopment Analysis (DEA) as a tool, aiming to obtain efficiency indices to support the decision making of public agents. The data used refer to the period from August 2018 to July 2019, in which the specialties of Medical Clinic, Surgical Clinic and Obstetrics were selected to compose the analysis inputs and outputs. The evaluation brings considerations and contributions regarding the public health problem in the state and in the country.